Role of Cardiac Magnetic Resonance Imaging in Hypocalcemia-Induced Dilated Cardiomyopathy in Pediatric Population - Garg, Ankit; Azad, Sushil; Kumar, Khemendra; Bhatia, Mona; Radhakrishnan, S. (Indian Journal of Radiology and Imaging, 2021)
Background Hypocalcemia is a rare reversible cause of dilated cardiomyopathy in pediatric population. Myocarditis is another more frequent cause of cardiomyopathy with overlapping presenting features. Cardiac magnetic resonance imaging (CMRI) is a vital modality capable of tissue characterization for the evaluation of cardiomyopathy. The present study is the first attempt to determine if any specific characteristics on CMR exist in patients with hypocalcemic dilated cardiomyopathy.Methods A retrospective analysis of 10 cases of hypocalcemic dilated cardiomyopathy (August 2012–August 2019), among which CMRI of nine patients were analyzed. Patients were categorized in to three categories; category 1 defined as absence of edema and late gadolinium enhancement (LGE), category 2 having edema only, and category 3 with presence of both edema and LGE. A diagnosis of myocarditis was considered if both edema and LGE were present.Results The mean age of the cohort was 5.5 ± 3.3 months. The mean ejection fraction of the cohort was 20.5 ± 6.85% that improved significantly to 35.22 ± 9.3% at the time of discharge. Five of nine patients had no edema or LGE (category 1), whereas two patients each were categorized into category 2 and 3. All cases in category 1 had normalized ventricular function on follow-up. One patient in category 2 had normal ejection fraction and one was lost to follow-up. Out of the two patients in category 3, there was one mortality and another was lost to follow-up. Of the six patients at follow-up (19 ± 11.0 months), the mean left ventricle ejection fraction improved to 56.5 ± 6.1%.Conclusion Hypocalcemic dilated cardiomyopathy has a favorable outcome on rapid initiation of treatment. CMR can be utilized for further prognostication of these patients. Absence of edema and LGE predicts a good outcome, whereas presence of LGE and/or edema either indicates a worse prognosis or an underlying coexistent myocarditis warranting an early myocardial biopsy.
Keywords: CMR; dilated cardiomyopathy; hypocalcemia; myocardial dysfunction; myocarditis; pediatric